2021
DOI: 10.1038/s43856-021-00039-7
|View full text |Cite
|
Sign up to set email alerts
|

Serology study after BTN162b2 vaccination in participants previously infected with SARS-CoV-2 in two different waves versus naïve

Abstract: Background The antibody response to SARS-CoV-2 mRNA vaccines in individuals with waning immunity generated by a previous SARS-CoV-2 infection, as well as the patterns of IgA and IgM responses in previously infected and in naïve individuals are still poorly understood. Methods We performed a serology study in a cohort of BTN162b2 mRNA vaccine recipients who were immunologically naïve (N, n = 50) or had been previously infected with SARS-CoV-2 (P.I.,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…One dose of vaccine received after COVID-19 is sufficient to produce peak antibody levels extremely quickly. These findings agree with the results of previous studies and go in line with the recommendation of second dose administration 6 months after recovering from COVID-19 [14][15][16][17][18][19][20][21][22][23][24][25][27][28][29][30]. Furthermore, these results can be explained by the limited humoral response to SARS-CoV-2 and the self-maintenance nature of the immune system.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…One dose of vaccine received after COVID-19 is sufficient to produce peak antibody levels extremely quickly. These findings agree with the results of previous studies and go in line with the recommendation of second dose administration 6 months after recovering from COVID-19 [14][15][16][17][18][19][20][21][22][23][24][25][27][28][29][30]. Furthermore, these results can be explained by the limited humoral response to SARS-CoV-2 and the self-maintenance nature of the immune system.…”
Section: Discussionsupporting
confidence: 92%
“…It has been confirmed that the anti-SARS-CoV-2 S1 RBD assay used in our study shows a strong correlation to antibody neutralization ability, allowing us to estimate the immunogenic potential of the BNT162b2 mRNA vaccine in different participant groups [11,19,21,25]. Antibody levels in non-COVID-19 participants reached as early as 3 weeks after the first dose were on average 18-fold higher than the test threshold, highlighting the vast immunogenic potential of the BNT162b2 vaccine.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations